Pemenuhan asupan gizi pada masyarakat “suku anak dalam (SAD)” yang menderita penyakit infeksi - Listautin Listautin; Mila Triana Sari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Infectious diseases in Jambi Province are still a health problem that is ranked second out of the ten largest diseases. Prevention of infectious diseases still needs to be done to reduce the increase in morbidity, namely by fulfilling nutritional intake.Purpose: To identify the relationship between the compliances of nutritional intake in the